Yield assessment and economic returns from agroforestry systems in sub-temperate region of Himachal Pradesh, India - Kumar, Pradeep; Thakur, C.L.; Rai, Pradeepen (Indian Journal of Agroforestry, 2020)
Different agroforestry systems existing in Kandaghat block of Solan district (H.P.) were identified and evaluated for biomass production and economic returns. Agri-silviculture (AS), Agri-silvipastoral (ASP), Agri-silivi-horticulture (ASH), Agri-horti-silviculture (AHS), Horti-pastoral (HP) and Silvi-pastoral (SP) were the prominent systems being practised in the area. Total biomass (AG+BG) of crops, grasses and trees were summed up to give a grand total biomass (C+G+T) of agroforestry system. The order of decrease in grand total biomass for different categories of farmers in AS was small (19.21 t ha-1yr-1) > medium (18.85 t ha-1yr-1) > marginal (18.28 t ha-1yr-1); in ASP medium (19.84 t ha-1yr-1) > marginal (18.48 t ha-1yr-1) > small (17.46 t ha-1yr-1); in ASH small (21.02 t ha-1yr-1) > marginal (17.48 t ha-1yr-1) > medium (16.83 t ha-1yr-1); in AHS medium (13.79 t ha-1yr-1) > marginal (13.12 t ha-1yr-1) > small (12.16 t ha-1yr-1); in HP medium (15.36 t ha-1yr-1) > small (13.34 t ha-1yr-1) and in SP medium (24.88 t ha-1yr-1) > small (23.24 t ha-1yr-1) > marginal (22.13 t ha-1yr-1). Net returns of marginal farmers decreased in the order of AHS (Rs. 297952 ha-1yr-1) > AS (Rs. 235059 ha-1yr-1) > ASH (Rs. 225557 ha-1yr-1) > ASP (Rs. 196173 ha-1yr-1) > SP (Rs.33232 ha-1yr-1), while for small farmers the order of decrease was ASH (Rs. 269744 ha-1yr-1) > AHS (Rs. 259336.01 ha-1yr-1) > HP (Rs. 242041 ha-1yr-1) > ASP (Rs. 210521 ha-1yr-1) > AS (Rs. 198888 ha-1yr-1) > SP (Rs. 43085 ha-1yr-1). In medium category, net returns exhibited order of AHS (Rs. 250870 ha-1yr-1) > HP (Rs. 232803 ha-1yr-1) > ASH (Rs. 223230 ha-1yr-1) > AS (Rs. 213595 ha-1yr-1) > AS (Rs.185707 ha-1yr-1) > SP (Rs. 39072 ha-1yr-1). Our findings manifested that agroforestry systems contribute greatly in biomass production as well as help in socio-economic upliftment of farmers.